Cyclic cohomology and noncommutative geometry - Cuntz, Joachim; Khalkhali, Masoud (Fields Institute communications, 1997)
Asymptotic morphisms on contact manifolds and index theory / Pradeep Alwis -- Noncommutative differential geometry and the structure of space time / Alain Connes -- Excision in periodic cyclic theory for topological algebras / Joachim Cuntz -- A closed model structure for differential graded algebras / J.F. Jardine -- Sur la K-th(c)♭orie multiplicative / Max Karoubi -- A survey of entire cyclic cohomology / Masoud Khalkhali -- Overview on Leibniz algebras, dialgebras and their homology / Jean-Louis Loday -- Straight chern character for Witt spaces / Henri Moscovici and Fangbing Wu -- Super-connections and non-commutative geometry / Victor Nistor -- Spectral flow in type I and II factors : a new approach / John Phillips -- A survey of asymptotic cyclic cohomology / Michael Puschnigg -- The higher [gamma]-index for coverings of manifolds with boundaries / Fangbing Wu